Penguatan Kearifan Lokal untuk Resolusi Konflik dan Upaya Bina Damai di Pulau Seribu Masjid - Suprapto Suprapto (JURNAL INDO-ISLAMIKA, 2011)
Identifying local traditions and wisdoms is essential in reducing conflicts and promoting peace within Muslim societies. Peaceful situation that is created from the preservation of local wisdoms within societies can store harmony and social cohesion and unity. The resolution of conflict that has been so far attempted rarely works out due to the inappropriate model taken. This paper discusses the conflict plot and critically analyses its resolution in ‘Pulau Seribu Masjid’ Lombok. It also observes how a number of local wisdoms, such as sesengak, perteke, and lelakaq, and local traditions that are well preserved can be employed to resolve th existing conflict and develop peace building.